(untitled) (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
Loyalty guarantees the company to continue to get consumers in the future. This becomes very important to be improved by the company to win the competition. The research was conducted in order to examine the effect of digital marketing and product quality on loyalty at the Gianyar Balinese Ethnic Traditional Clothing Store in Gianyar Regency. The sampling technique was carried out by random sampling. The results of the deterministic analysis show that 82.7% of customer loyalty is due to a combination of digital marketing and product quality. Significa test results for partial menus are also very positive for members of digital marketing. Product quality has a significant positive effect on customer quality. Simultaneous effect tests show that digital marketing is based on the Three Numbers concept and product quality has a positive and significant effect on customer loyalty.